Tradisi Pengelolaan Tata Ruang Kampung Kuta Desa Karangpaninggal Kecamatan Tambaksari Kabupaten Ciamis - Dewi Ratih; Sudarto Sudarto; Yadi Kusmayadi; Ine Sinta Nia; Fanny Astridha; Muhamad Alpian; Salma Rahmillah (Universitas Galuh, 2026)
This study examines the spatial management traditions of the Kampung Kuta indigenous community in Ciamis, exploring the underlying cultural values and their implications for environmental sustainability. Using a qualitative descriptive case study approach, data were collected through observations, interviews, and documentation. The results reveal that Kampung Kuta’s spatial system is governed by local wisdom known as pamali, which functions as both a social norm and a spatial regulation. These rules dictate the use of natural materials for stilt houses and uniform settlement patterns that reflect simplicity and social cohesion. Furthermore, the strictly preserved sacred forest plays a vital role in maintaining ecosystem balance and water conservation. The study concludes that these traditions form an integrated socio-cultural and ecological system that serves as a model for sustainable spatial planning. Pamali operates simultaneously across normative, symbolic, and ecological dimensions, offering valuable insights for modern sustainable management.